Potensi Neptunia oleracea Lour. pada fitoremediasi drainase asam tambang batubara - Rika Nasution; Singgih Tri Wardana; Nina Tanzerina; Sri Pertiwi Estuningsih; Juswardi Juswardi (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
Environmental problems in coal mining activities include acid mine drainage (AMD). Efforts to overcome the impact of AMD waste can be done by means of phytoremediation. Neptunia oleracea Lour. is one type of aquatic plant that has the potential to adapt and accumulate heavy metals. So it is necessary to do research with the aim of knowing the potential of N. oleracea in AMD phytoremediation. The phytoremediation potential of N. oleracea used a completely randomized design (CRD): without AMD as control (0%), with AMD concentrations of 25%, 50%, 75% and 100%. The results showed that N. oleracea has the potential to increase pH by 0.0322/day and reduce Fe content by 0.4760 mg/l/day, Mn 0.5776 mg/l/day, sulfate 0.4809 mg/l/day and reduce TSS by 0.0818 mg/l/day, at 100% AMD concentration. It can be concluded that N. oleracea has potential as an AMD phytoremediation agent to be developed in system constructed wetlands (CWs).